The Effect of HRIS Information System Service Quality on Employee Work Productivity: The Role of Green Behavior as a Moderation Variable in the Regional Office of the Directorate General of Treasury of West Sulawesi Province - Husni; Yuniawan Hari Raharjo; Hari Yeni; Muhammad Aqil (Research and Social Study Institute (ReSSI), 2026)
Digital transformation in human resource management requires public organizations to provide information systems that are not only technically reliable but also capable of supporting employee efficiency and sustainability. This study aims to analyze the effect of Human Resource Information System (HRIS) service quality on employee work productivity and examine the role of green behavior as a mediating variable at the Regional Office of the Directorate General of Treasury of West Sulawesi Province. The study used a quantitative approach with an explanatory design. All 64 employees were selected as respondents through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares using SmartPLS. The results showed that HRIS service quality had a positive and significant effect on employee work productivity with a path coefficient of 0.312, a t-statistic of 2.986, and a p-value of 0.003. HRIS service quality also had a positive and significant effect on green behavior with a coefficient of 0.751, a t-statistic of 9.214, and a p-value <0.001. Furthermore, green behavior had a positive and significant effect on work productivity, with a coefficient of 0.418, a t-statistic of 4.307, and a p-value <0.001. The indirect effect of HRIS service quality on productivity through green behavior was also significant, with a coefficient of 0.314, a t-statistic of 4.081, and a p-value <0.001. The model explained 71.2% of the variation in employee work productivity. These findings confirm that responsive, easy-to-use, and tailored HRIS services can increase productivity directly and through fostering resource-efficient, orderly, and sustainability-oriented work behaviors.